2010
DOI: 10.1186/1471-244x-10-2
|View full text |Cite
|
Sign up to set email alerts
|

The cost of relapse and the predictors of relapse in the treatment of schizophrenia

Abstract: BackgroundTo assess the direct cost of relapse and the predictors of relapse during the treatment of patients with schizophrenia in the United States.MethodsData were drawn from a prospective, observational, noninterventional study of schizophrenia in the United States (US-SCAP) conducted between 7/1997 and 9/2003. Patients with and without relapse in the prior 6 months were compared on total direct mental health costs and cost components in the following year using propensity score matching method. Baseline p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
180
0
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 227 publications
(186 citation statements)
references
References 22 publications
3
180
0
3
Order By: Relevance
“…The largest portion of the patients was from the European part of the W‐SOHO study, in which there was no relationship between age at onset and relapsing (Haro et al, 2006). Three studies reported a significant relationship between age at onset and relapsing: Ascher‐Svanum et al (2010) found that those with relapse during the 1‐year follow‐up period were over 2 years younger at onset than those not having relapse and (Altamura et al’s (2001) results showed a 2.9‐year difference. Eaton's results in India, however, showed that age at onset above 25 increased the risk of relapsing (Eaton, Thara, Federman, & Tien, 1998).…”
Section: Resultsmentioning
confidence: 99%
“…The largest portion of the patients was from the European part of the W‐SOHO study, in which there was no relationship between age at onset and relapsing (Haro et al, 2006). Three studies reported a significant relationship between age at onset and relapsing: Ascher‐Svanum et al (2010) found that those with relapse during the 1‐year follow‐up period were over 2 years younger at onset than those not having relapse and (Altamura et al’s (2001) results showed a 2.9‐year difference. Eaton's results in India, however, showed that age at onset above 25 increased the risk of relapsing (Eaton, Thara, Federman, & Tien, 1998).…”
Section: Resultsmentioning
confidence: 99%
“…A large proportion of the total health care costs of schizophrenia and BD are due to hospitalizations (7,8). Rehospitalizations are costly and are markers of reduced function and quality of life of patients with psychotic disorders and their families (9)(10)(11). Internationally the concept of recovery has had a growing influence on mental health services (12) emphasizing patients self-direction, empowerment and responsibility (13).…”
Section: Introductionmentioning
confidence: 99%
“…Both partial adherence and non-adherence to oral antipsychotic medication are challenging aspects of schizophrenia treatment, and are associated with increased risk of relapse, rehospitalisation and suicide (Ascher-Svanum et al 2010;Novick et al 2010;Higashi et al 2013). Non-adherence to oral antipsychotic medication has been shown to result in an almost five-fold increase in the risk of relapse (Robinson et al 1999).…”
Section: Introductionmentioning
confidence: 99%